Safety and efficacy of antithrombotic therapy according to stroke and bleeding risk in patients with atrial fibrillation and acute coronary syndrome or PCI: insights from AUGUSTUS. (25th November 2020) - Harskamp, R; Lopes, R.D; Li, Z; Wojdyla, D; Goodman, S.G; Aronson, R; Windecker, S; Mehran, R; Granger, C.B; Alexander, J.H
Abstract: Background: The AUGUSTUS trial showed that patients with atrial fibrillation (AF) and acute coronary syndrome (ACS) and/or PCI treated with a P2Y12 inhibitor and apixaban resulted in less bleeding and comparable ischemic events compared with regimens that included a vitamin K antagonist (VKA), aspirin, or both. We assessed the effect of apixaban versus VKA and aspirin versus placebo according to patients' baseline risk of stroke and bleeding. Methods: AUGUSTUS randomized 4614 patients in a two-by-two factorial design to open label apixaban or VKA and blinded aspirin or placebo. The primary endpoint was major or clinically relevant nonmajor (CRNM) bleeding over 6 months of follow-up. The effects were assessed stratified by baseline CHA2DS2-VASc and HAS-BLED score using Cox proportional hazards models. Results: 4386 patients were included for this analysis. The median age was 71 (64–77) years, 29.4% were female, 81.7% had a CHA2DS2-VASc score≥3, and 66.8% a HAS-BLED score≥3. As shown in the table, rates of bleeding were lower with apixaban (vs VKA) irrespective of baseline bleeding risk (p-value interaction: 0.23). Aspirin (vs placebo) was associated with increased bleeding irrespective of baseline risk (p-value interaction: 0.88). Apixaban use was associated with a lower risk of death or hospitalization without a significant interaction with stroke risk (p-value of interaction=0.53). No differences were found for ischemic outcomes. Conclusion: An antithrombotic regimen including a P2Y12 inhibitor and apixaban is associated with less bleeding and hospitalization compared to a regimen with VKA, aspirin, or both with results consistent across CHA2DS2-VASc, and HAS-BLED scores. Our findings support the use of apixaban and a P2Y12 inhibitor without aspirin during the first 6 months for most patients with AF and ACS and/or PCI, regardless of stroke and bleeding risk. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): The Augustus trial was sponsored by Bristol-Myers Squibb and Pfizer, Inc